2016
DOI: 10.17722/ijme.v7i2.847
|View full text |Cite
|
Sign up to set email alerts
|

Shaken But Unruffled: Stories of Psychologically Distressed Public Secondary School Teachers

Abstract: Psychological distress is a global phenomenon that affects not only the psychological and physical well-being but also the profession of  teachers  around the world. The purpose of this multiple case study was to explore the experiences of psychologically distressed public secondary school teachers, their coping strategies, and insights they can share to their peers and to the academe in general. The participants of this inquiry were five female teachers from the public secondary schools of Davao del Norte div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 141 publications
0
2
0
Order By: Relevance
“…Fitting themselves to the job entails making them comfortable while performing their job. To some extent, this also has some bearing with the disengagement theory which presumes detachment from and avoidance of complicated and stressful situations by elderly people, theory developed by Cumming, Dean, Newell and McCaffrey (1960) and utilized in the researches of Gobeski and Beehr (2009)[31], Maestas (2010) [49], Olmedo and Gempes, 2016 [60], and Wang, et al, ( 2008) [84].…”
Section: 21mentioning
confidence: 99%
“…Fitting themselves to the job entails making them comfortable while performing their job. To some extent, this also has some bearing with the disengagement theory which presumes detachment from and avoidance of complicated and stressful situations by elderly people, theory developed by Cumming, Dean, Newell and McCaffrey (1960) and utilized in the researches of Gobeski and Beehr (2009)[31], Maestas (2010) [49], Olmedo and Gempes, 2016 [60], and Wang, et al, ( 2008) [84].…”
Section: 21mentioning
confidence: 99%
“…Findings from various studies demonstrated that spirituality alleviates fatigue and psychological distress related to it [ 19 ]. Among schoolteachers, personal spirituality was found to provide teachers with coping strategies in managing challenges [ 20 ]. Similarly, the impact of prayer as well as meditation and spiritual techniques were found to largely diminish the symptoms of burnout among a sample of teachers in a Catholic school [ 21 ].…”
Section: Introductionmentioning
confidence: 99%